Analisis Pengangguran Terhadap Tindakan Kriminalitas di Kota Bekasi - Kurnia Nurul Azmi; Salsabila Putri Azzahra; Vanesa Kusuma Dewi; Yuarini Wahyu Pertiwi (Observasi : Jurnal Publikasi Ilmu Psikologi, 2024)
This study aims to determine whether unemployment affects criminality in Bekasi City through a literature study approach. Unemployment is often considered as one of the main factors driving crime, as economic limitations can force individuals to commit criminal acts as a means of survival. This study collected and reviewed various previous studies, including journal articles, research reports, and relevant statistical data, to explore the relationship between unemployment and crime. The results of the literature review show that unemployment is not the only cause of crime. Rather, there are other factors that influence crime rates, such as education, socio-economic conditions, and local government policies. The findings are expected to provide insights or a deeper understanding of the social dynamics that influence criminality